EFL COLLEGE STUDENTS' SPEAKING CONSTRAINS IN RESEARCH PROPOSAL SEMINAR PRESENTATION - Sinarman Jaya; Dian Susyla; Hartania Yoanda Agustin (Fakultas Keguruan dan Ilmu Pendidikan, 2021)
This study is aimed to find out English as a Foreign Language (EFL) college students’ speaking constrains in research proposal seminar presentation. The design of the research was a qualitative descriptive. The subjects of this research were 29 students of English Study Program of Muhammadiyah of Bengkulu who presented their proposal on April 2020 – June 2020. The researcher used observation checklist as the instrument of this research. The checklist was designed based on Gan (2012). The questions were divided into five aspects; limited number of vocabulary, hard to apply grammar rules, and not perfect pronunciation and Intonation. The findings revealed that speaking constrains encountered by the students of English Education Study Program of Muhammadiyah University of Bengkulu in proposal seminar presentation were limited number of vocabulary, hard to apply grammar rules, not perfect pronunciation and intonation. It is suggested that students take a lot of practices and make a good preparation. Structure your talk by the same order that you have structured your research proposal. Moreover, you can also attend English offline academic seminar and watch English seminar on You Tube more frequently.Key Words: EFL college students, speaking constrains, proposal seminar.